Perceptions of the online learning experience among medical students during COVID-19 - Shahrir, Shahida Athirah; Razman, Amalia Izzati; Anuar, Muhammad Ashraf Fithri; Abdullah, Muhammad Haikal; Ahmad Ashhar, Muhammad Ikmal Arif; Ahmad Haridan, Ahmad Zhareff Emir; Nor Azlan, Nur Khairunnisa; Mohamad, Mohammad Muaz; Shaik Mohd Nizam, Nur Alia Iman; Johari, Muhammad Luqman ‘Afif; Zulkifli, Ahmad Najmi Abid; Zamani, Muhammad Razin; et al. (2021)
Social gatherings have been limited during the COVID 19 pandemic to reduce the transmission of viruses. Many academic institutions have shifted their classes from traditional methods into online remote teaching and learning sessions. Since neither the students nor lecturers were familiar with this setting, the delivery of medical education has undoubtedly impacted as the lectures, clinical placements and key examinations were discontinued. Many adjustments need to be made in order to make sure that the online teaching is held properly. This study was conducted to investigate the perceptions of online learning experience among medical students during the pandemic. An online survey was distributed to 158 medical students from Year 1 and Year 2 of International Islamic University Malaysia (IIUM) from July 2021 till August 2021. The Learning Community Scale and Student Support Scale based on Course Experience Questionnaire (CEQ) were applied to measure the participants' perceptions. The data were analysed using Statistical Package for the Social Sciences (SPSS) version 26. Based on the Learning Community scale, higher response values signified better feelings towards the learning community. The average scores of all five questions were high level (3.68-4.36 on 5-Likert scale), suggesting that the participants were feeling well towards their learning community. Likewise, higher response values in the Student Support scale indicated that better student support is perceived. The average scores of all five questions were also high (3.11-4.31 on 5-Likert scale), indicating that the respondents perceived an adequate amount of student support. In conclusion, the study conjectured positive perceptions towards their learning experience during COVID-19 pandemic among the students despite the sudden shift from physical to online teaching and learning sessions. However, broader ethnic groups and larger sample sizes might be useful for more precise and reliable future results.